The Ovidian Fable of Philomela Reviewed by the Middle Ages: from Chrétien de Troyes to Alfonso X - Botero García, Mario (Íkala, Revista de Lenguaje y Cultura, 2015)
This paper shows the contrast between the French and Castilian translations of Philomela, one of the most known fables of Ovid’s Metamorphoses, by Chrétien de Troyes and Alfonso X. Through the analysis and comparison of three moments of the text, we can see how the ancient material is treated according to the particular context in which the translations appear. The French version emphasizes a courtly dimension where the female character is highly valued. In the other hand, the Castilian version indicates a rationalization of the Ovidian fable, which is evaluated according to a political and historical vision. It can be seen that medieval translations are not servile with respect to the source but show great freedom in the selection and combination of elements.